Implementasi E-training pada Pelatihan Tenaga Pelatih Kesehatan Angkatan 7 di Bapelkes Semarang - Nisrina Rafifah Haya; Joko Sutarto (Universitas Pahlawan Tuanku Tambusai, 2024)
Health Trainer Training is general training for trainers given to professional or expert to become facilitators. The 7th Health Trainer Training at Bapelkes Semarang in its implementation uses a full online training method. This study aims to describe the planning, implementation, evaluation, and the supporting and inhibiting factors of the training. This study uses a qualitative descriptive method with data collection through interviews, observations, and documentation. The subjects of this study consisted of 1 leader, 2 organizers, 3 facilitators, and 2 participants. The data validity technique for this study uses source triangulation and technique triangulation. Data analysis uses data collection, reduction, presentation, and conclusion. The results of the study show (1) planning: setting goals, materials, target group conditions, and learning resources, namely facilitators and learning media. (2) implementation: training program activities, facilities and infrastructure, teaching materials, learning methods, learning outcome assessment systems, and time allocation. (3) training evaluation is carried out through the distribution of evaluation forms, pre-tests and post-tests, assignments, and microteaching assessments. The supporting factors are the organizers provides good resources, support from participating agencies, and internet network that works well. The inhibiting factors are that participants are still given a workloadand the participants' internet network is not fully working properly.